A semiotic analysis of print advertisements in the Malaysian General Elections 2013 Campaign - Mokhtar, Aida (2013)
The campaigning in the General Elections 2013 proved to be an interesting moment for Malaysians with the existence of close competition between the political parties. A semiotics analysis was carried out on selected unduplicated print advertisements taken from Utusan Malaysia and the New Straits Times. There were three analysts from the main ethnic groups in Malaysia: the Malay, Chinese and Indian groups. The findings of this research study found that the analysts had different interpretations of the print advertisements in terms of the themes and signs identified.